Privacy and confidentiality in medicine: what does the General Data Protection Regulation say about health information access - Loureiro, Rodrigo Miguel (2022)
The digital revolution in health services has provided new opportunities for the development of quality care, research of new treatments, and better usage of resources. Most of the information that is currently digitally shared was previously shared on paper, thus raising new security and privacy challenges and digital threats. There were about 28 different data protection laws based on the 1995 EU Data Protection Directive, which was drawn up 20 years ago, before the widespread introduction of the Internet and growing privacy concerns. Despite technological advances, the existing regulation has remained stagnant and increasingly inadequate to protect individual or organizational data. Given this need, the Regulation 2016/679 of the European Parliament and Council of 27 April 2016 was elaborated and approved. The General Data Protection Regulation introduced significant changes to the legal framework for the protection of personal data within the European Union, laying down rules on the protection of individuals regarding the processing of personal data and its free movement. These changes should influence the way health care providers handle health data, both in the provision of healthcare and for research purposes.